DESIGN OF EXPERIMENT VERTICAL LIFTER UNTUK MENINGKATKAN EFISIENSI MOLD - Christoporus Lingga Arjuna; Kaswadi, Agung; Widagdo, Budi Hargo (Technologic, 2025)
This study was conducted on an injection plastic mold at a motorcycle manufacturing company in Indonesia. Along with consumer demands, the company is required to always develop the latest models. As models continue to change, the company is faced with demands to improve mold efficiency. This research aims to improve mold efficiency by shrinking mold dimensions in terms of lifter component usage using an innovative vertical lifter design. The method used in this research is Design of Experiment by using the vertical lifter design in designated mold. The experiment focused on changing the lifter mechanism from an angled rod to release the undercut to a perpendicular rod with an angled groove on the head. Simulation of the vertical lifter design showed a reduction in the dimensions of the test mold base so that the material cost of the test mold base could be reduced by 30%. The research conducted contributes to efforts to improve mold efficiency